Selected Behaviors and Addiction Risk Among Users of Urban Multimedia Games - Grajek, Mateusz; Olszewski, Łukasz; Krupa-Kotara, Karolina; Białek-Dratwa, Agnieszka; Sas-Nowosielski, Krzysztof (Frontiers in Psychology, 2022)
Introduction. The rapid development of technology has led to the transfer of entertainment to the virtual world. Many games and multimedia applications use the so-called augmented reality. With the development of a new technological branch, a new health problem has emerged, which is infoholic addiction, attracting people with the specific functionality that is cyberspace and the virtual world. Objective. The study aimed to assess health behaviors and the risk of addiction among users of urban multimedia games. Research methodology. The study was conducted among players1134 of urban multimedia games - Pokemon GO, in the period March- June 2021. 990 correctly completed questionnaires were included in the final analyses. The author's questionnaire was used in the study, which included two standardized measurement scales in the Polish abbreviated version: a questionnaire of emotions and sensations associated with electronic entertainment and a questionnaire on addiction to electronic forms of entertainment. Statistica 13.0 program was used for statistical processing of the data. The probability level was p<0,05. Results. The profile of the gamer was identified as male, aged 18-30 years, with secondary education (more rarely higher), not in a relationship, living in a city of more than 100 thousand inhabitants - 60.1% of gamers met these criteria. Respondents played urban multimedia games daily (84.7%). About 26.3% of respondents played this type of game 2-3 hours a day. In terms of physical fitness, 64.3% of respondents felt that physical fitness had improved as a result of playing multimedia urban games. In terms of mental condition, most of the respondents said that nothing had changed (55.3%). It was observed that 72.3% of respondents had some risk of addiction to urban multimedia games. Conclusions. Users of urban multimedia games were usually adult men living in big cities. It was also shown that the defined profile of the player was characterized by a higher risk of addiction to electronic forms of entertainment. It was observed that the respondents most often played urban multimedia games every day in a maximum of two-hour sessions.